Correlation between epidermal growth factor receptor mutations and nuclear expression of female hormone receptors in non-small cell lung cancer: a meta-analysis - He, Qihua; Zhang, Mingzhe; Zhang, Jianrong; Chen, Ying; He, Jiaxi; Shen, Jianfei; Liu, Yang; Zhong, Shengyi; Jiang, Long; Yang, Chenglin; Zeng, Yuan; Guo, Minzhang; et al. (Journal of Thoracic Disease, 2015)
Background: Compared with male, female non-small cell lung cancer (NSCLC) patients have better response when treated with epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs), suggesting a potential association between female hormones and EGFR mutation. However, the results provided by previous studies were inconclusive and controversial. We sought to examine the link between the expression of nuclear female hormone receptors and EGFR mutations in NSCLC. Methods: Electronic databases were used to search the relevant articles. The involved hormone receptors included estrogen receptor (ER) and progesterone receptor (PR). The primary endpoint was the occurrence of ER/PR expression and EGFR mutation in NSCLC patients. Results: Five studies fulfilled the criteria and were included in our analysis. Patients with high ER-β expression had higher positive EGFR mutation than low ER-β patients (44.2% vs. 23.7%), and there was a significant difference between the two groups [odds radio (OR) 3.44, 95% confidence interval (CI): 2.40 to 4.93, Z=6.72, P